Recent advances in metals and metal oxides as catalysts for vanadium redox flow battery: Properties, structures, and perspectives. (10th June 2021) - Lv, Yanrong; Han, Chao; Zhu, Ye; Zhang, Tianao; Yao, Shuo; He, Zhangxing; Dai, Lei; Wang, Ling
Graphical abstract: Highlights: The research progress of metal and metal oxide catalysts in VRFB in recent years was reviewed. The metal and metal oxide catalysts were classified and their structures were studied. Analyze and compare different catalysts to help improve battery performance. 4 The design and development of VRFB catalyst were prospected. Abstract: Vanadium redox flow battery (VRFB) is a kind of battery with wide application prospect. Electrode material is one of the key components of VRFB, and its stability directly affects the performance of battery. Among all kinds of electrode materials, carbon-based material has the best comprehensive properties. However, carbon-based electrodes still have disadvantages such as poor hydrophilicity and low electrochemical activity which need to be improved. One of the effective ways to improve the performance of electrode is to modify carbon-based material with metals and metal oxides. The metal catalysts have excellent electrical conductivity and high catalytic activity. The metal oxide catalysts have the advantages of low cost, wide variety and strong oxidizing properties. This work introduced the application of metal and metal oxide modified electrodes in VRFB in recent years, classified the catalysts, studied their catalytic performance and mechanism. The metal catalysts were reviewed from precious metals and base metals. The metal oxide catalysts were classified and discussed according to the similar properties of the same group elements. This work compared different modification methods, summarized the research progress of metal and metal oxide modification, and proposes the future development direction of electrodes and catalysts.